Identification and sequencing of cDNA clones encoding the granule-associated serine proteases granzymes D, E, and F of cytolytic T lymphocytes. - Jenne, D (1988)
Cytoplasmic granules of cytolytic T lymphocytes contain at least six related serine esterases (granzymes) that are released together with perforin, a pore-forming protein related to complement component C9, during target-cell lysis. Polyclonal antibodies were used to isolate a large number of cDNA clones from an expression library derived from cytolytic-T-cell mRNA. Three distinct full-length cDNA clones coding for granzymes D, E, and F were identified by restriction site mapping and nucleotide sequencing. The three deduced amino acid sequences are highly similar to one another (between 72% and 90% amino acid identities) and to the sequences of granzymes B and C, cathepsin G, and rat mast-cell proteases I and II (between 43% and 57% amino acid identities). Cysteine residues capable of forming intramolecular disulfide bonds are conserved, as are the catalytic-site residues characteristic of serine proteases. Comparison of the cDNA-derived protein sequences with the amino termini of the isolated granzymes provides evidence that they are stored in a fully processed, activated form after removal of the signal peptide and two additional residues (propeptide) at the amino terminus. Immunoelectron microscopic studies demonstrated that granzymes D, E, and F are present in the same morphologically distinct cytoplasmic granules in which perforin has been found previously.